(untitled) (Papeles, 2019)
“I must set sail before Napoleon tries to conquer London, winter has been hard in Madrid. From the beginning of spring I have enlisted as a first gunner on a pirate ship. An old friend, a German Captain, has given me a map and a letter for some gentlemen in Memel. I have been serving among men of his Majesty Charles III. A betrayal has put my name among his enemies."